2004
DOI: 10.1534/genetics.166.4.1923
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Genetic Linkage Maps With Pachytene Chromosome Structure in Maize

Abstract: Genetic linkage maps reveal the order of markers based on the frequency of recombination between markers during meiosis. Because the rate of recombination varies along chromosomes, it has been difficult to relate linkage maps to chromosome structure. Here we use cytological maps of crossing over based on recombination nodules (RNs) to predict the physical position of genetic markers on each of the 10 chromosomes of maize. This is possible because (1) all 10 maize chromosomes can be individually identified from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
59
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 34 publications
8
59
0
Order By: Relevance
“…Advances in FISH techniques have allowed specific maize loci to be detected, anchoring the genetic map to a physical location (Koumbaris and Bass 2003;Anderson et al 2004;Kato et al 2006;Wang et al 2006). In the related Sorghum species, the use of BACs has allowed detailed cytogenetic maps to be developed (Zwick et al 1998;Islam-Faridi et al 2002;Kim et al 2002), opening up the possibility of cytogenetic examination of chromosomal rearrangements among species in this genus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in FISH techniques have allowed specific maize loci to be detected, anchoring the genetic map to a physical location (Koumbaris and Bass 2003;Anderson et al 2004;Kato et al 2006;Wang et al 2006). In the related Sorghum species, the use of BACs has allowed detailed cytogenetic maps to be developed (Zwick et al 1998;Islam-Faridi et al 2002;Kim et al 2002), opening up the possibility of cytogenetic examination of chromosomal rearrangements among species in this genus.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in chromosome spreading procedures, development of a collection of DNA elements that can be used as fluorescence in situ hybridization (FISH) probes to identify each chromosome (Kato et al 2004), and detection of specific genetic loci on chromosomes (Koumbaris and Bass 2003;Anderson et al 2004;Kato et al 2006) have expanded the number of cytological tools available to maize researchers.…”
mentioning
confidence: 99%
“…Because the total EXPEN 2000 map length for chromosome 1 differs from the corresponding RN-cM map length (Table 1), the EXPEN 2000 map positions were adjusted proportionally for each arm to fit the length of the RN-cM map following the procedures described by Anderson et al (2004). These adjusted values are now termed the RN-cM values for each marker (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Anderson et al (2004) reported a new approach for locating mapped loci on maize pachytene chromosomes. This technique depends on first mapping the frequency and location of recombination nodules (RNs) on synaptonemal complexes (SCs, pachytene bivalents).…”
Section: W Hile Linkage Maps Accurately Describe Genementioning
confidence: 99%
See 1 more Smart Citation